THE UTILIZATION OF LAMINATED PETUNG BAMBOO FOR DOOR FRAME - Maliakhi Pasaribu; Santoso Sri Handoyo (Jurnal Pensil : Pendidikan Teknik Sipil, 2023)
Petung bamboo is one of the alternatives to wood that is needed due to the decreased availability of wood in the forest for construction. The objective of this research was to determine whether Petung bamboo could substitute wood in door frame. Research has been carried out to propose alternate methods of using bamboo to produce door frame that are environmentally friendly. Engineering research using experimental methods is conducted. The data collection technique was carried out using test specimens for specific gravity test, compressive strength test, and flexural strength test to obtain the strength value of the petung bamboo laminated door frame product which will later be compared with door frames made of wood on the market. Based on the findings of the research, Petung bamboo laminated door frame, which also made from petung bamboo laminated beam, had the specific gravity value of 0.646 g/mm2, the compressive strength of 51.34 MPa, and the optimum flexural strength of 87.6708 MPa. The values of specific gravity test, compressive strength test, and flexural strength test are comparable to the class II of wood strength and applicable to use as door panels based on PKKI 1961